2010
DOI: 10.1016/s1001-9294(10)60044-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intracoronary Infusion of Bone Marrow Mononuclear Cells or Peripheral Endothelial Progenitor Cells on Myocardial Ischemia-reperfusion Injury in Mini-swine

Abstract: Transplantation of either MNC or EPC may be beneficial to cardiac systolic function, but might not has obvious effect on diastolic function. Intracoronary infusion of EPC might be better than MNC in controlling infarction size. Both MNC and EPC may stimulate angiogenesis, inhibit fibrogenesis, and differentiate into myocardial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…It is also important to note that it might not be appropriate to make comparisons between cell dosing studies that have used different routes of administration. Furthermore, although many preclinical studies [8][9][10][11] and clinical trials [12][13][14][15][16][17][18][19][20] have examined other cell types, such as bone marrow-derived mononuclear cells (BMMNCs), c-kit + cardiac stem cells, and cardiac CD105 + culture-expanded MSCs (cardiosphere-derived cells), they did not compare the cell doses but, rather, single doses with different cell products or placebo.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…It is also important to note that it might not be appropriate to make comparisons between cell dosing studies that have used different routes of administration. Furthermore, although many preclinical studies [8][9][10][11] and clinical trials [12][13][14][15][16][17][18][19][20] have examined other cell types, such as bone marrow-derived mononuclear cells (BMMNCs), c-kit + cardiac stem cells, and cardiac CD105 + culture-expanded MSCs (cardiosphere-derived cells), they did not compare the cell doses but, rather, single doses with different cell products or placebo.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Immunosuppression for MSCs might be redundant because these cells are considered by some to be immunoprivileged. 31 However, MSCs do interact with the immune system, play a role in immunomodulation, 32,33 and even elicit immune responses in vivo. 34 We performed a post hoc meta-regression of cell source for MSCs alone to establish whether there was any evidence of immune privileged properties for MSCs in cardiac repair.…”
Section: Autologous Versus Allogeneic Cell Therapymentioning
confidence: 99%
“…In another study, the intramyocardial injection of EPC in a swine model of AMI reduced the scar formation and prevented the left ventricular dysfunction after AMI, providing encouraging outcomes in favoring the application of EPCs as a potential therapy in clinical trials [105,106] (Figure 5). In the human studies performed by Li et al [108] and Lasala et al [107] it has been shown that intracoronary infusion of hEPC in patients with AMI were associated with the migration and incorporation of hEPCs in the infarcted tissue, a reduction of infarct size, and secretion of angiogenic growth factors including VEGF, SDF-1, and IGF-1, which produced more capillarity and higher transdifferentiation of cells to cardiac progenitor cardiomyocytes [107,108]. Moreover, these hEPCs also reduced apoptosis of endothelial cells and increased myocardial viability in the infarcted area [109,110].…”
Section: Clinical Translation Of Epc Therapymentioning
confidence: 99%